2021
DOI: 10.3389/fonc.2021.627158
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Clinical Value of CT-Guided 125I Brachytherapy for Pain Palliation in Patients With Breast Cancer and Bone Metastases After External Beam Radiotherapy Failure

Abstract: Objectives: To evaluate the feasibility and clinical value of CT-guided iodine-125 (125I) brachytherapy for pain palliation in patients with breast cancer and bone metastases after external beam radiotherapy failure.Methods: From January 2014 to July 2016, a total of 90 patients, who had received the standard therapies for bone metastases but still suffered moderate-to-severe pain, were retrospectively studied. About 42 patients were treated with both 125I brachytherapy and bisphosphonates (Group A), and 48 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Very similar results had been observed in some previous studies [288]. Moreover, the literature supports that iodine can also be used in photoimmunotherapy [289] and brachytherapy [290,291] and has potential in targeted radionuclide therapy [292]. A very interesting application of iodine is in 125I seeds, which can be implanted into a patient's lesion to provide treatment, improve the treatment's effects, reduce adverse reactions, and better the quality of life.…”
Section: Iodinesupporting
confidence: 77%
“…Very similar results had been observed in some previous studies [288]. Moreover, the literature supports that iodine can also be used in photoimmunotherapy [289] and brachytherapy [290,291] and has potential in targeted radionuclide therapy [292]. A very interesting application of iodine is in 125I seeds, which can be implanted into a patient's lesion to provide treatment, improve the treatment's effects, reduce adverse reactions, and better the quality of life.…”
Section: Iodinesupporting
confidence: 77%
“…Although previous studies [26,28] reported that due to osteosclerosis, OBMs were more difficult to puncture than osteolytic metastases, our center's clinical experience was that an ISI needle was used in conjunction with medical drills for puncturing lesion sites; this greatly reduced the difficulty of puncture, and the technical success rate was 100%. During the operation, CT or CBCT guidance clearly showed the volume of the tumor and the location of vital organs, making the entire operation safer and more accurate.…”
Section: Discussionmentioning
confidence: 98%